Elementary Technical Mathematics

Published by Brooks Cole
ISBN 10: 1285199197
ISBN 13: 978-1-28519-919-1

Chapter 6 - Section 6.3 - Equations with Parentheses - Exercises: 12

Answer

y=-3

Work Step by Step

Simplifying 27 + -8(2 + -1y) = -13 27 + (2 * -8 + -1y * -8) = -13 27 + (-16 + 8y) = -13 Combine like terms: 27 + -16 = 11 11 + 8y = -13 Solving 11 + 8y = -13 Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '-11' to each side of the equation. 11 + -11 + 8y = -13 + -11 Combine like terms: 11 + -11 = 0 0 + 8y = -13 + -11 8y = -13 + -11 Combine like terms: -13 + -11 = -24 8y = -24 Divide each side by '8'. y = -3 Simplifying y = -3
Update this answer!

You can help us out by revising, improving and updating this answer.

Update this answer

After you claim an answer you’ll have 24 hours to send in a draft. An editor will review the submission and either publish your submission or provide feedback.